1991
DOI: 10.1093/infdis/164.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc-Reversible Antimicrobial Activity of Neutrophil Lysates and Abscess Fluid Supernatants

Abstract: There is some evidence to suggest that microbial growth inhibition may occur in chronic abscesses. A substance perhaps responsible for this phenomenon is calprotectin, a neutrophil cytoplasmic protein that inhibits microbial growth and that belongs to a class of proteins often having specific binding sites for zinc. In the present study, the suppressive effects of either human or mouse neutrophil lysates on Candida albicans growth were found to be completely reversed by micromolar quantities of zinc but not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 26 publications
5
114
1
1
Order By: Relevance
“…However, the antiviral mechanism of neutrophils in host defense has not been investigated in detail. Recent studies indicated that neutrophils produced calprotectin as an antibacterial and antitumor protein (5,24,32,42), and that the antibacterial and antitumor activities of calprotectin were reversibly reduced by ZnS0 4 (5, 32). To assess the involvement of calprotectin in the inhibitory effect of neutrophils on influenza virus propagation, neutrophils and ZnS04 were added to MOCK cell cultures infected with influenza virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the antiviral mechanism of neutrophils in host defense has not been investigated in detail. Recent studies indicated that neutrophils produced calprotectin as an antibacterial and antitumor protein (5,24,32,42), and that the antibacterial and antitumor activities of calprotectin were reversibly reduced by ZnS0 4 (5, 32). To assess the involvement of calprotectin in the inhibitory effect of neutrophils on influenza virus propagation, neutrophils and ZnS04 were added to MOCK cell cultures infected with influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed by applying neutrophilic leukocytosis in tumor-bearing mice and neutrophil activation by tMLP in vivo to elucidate the roles of neutrophils as an effector cell population in the host defense against influenza virus infection. Furthermore, recent studies have indicated that neutrophils produce cal protectin as an antibacterial, antifungal, and antitumor protein (10,24,32,42), suggesting that calprotectin has a new mechanism of action based on a depletion of Zn ++• In this study, the contribution of calprotectin to the inhibitory effect of neutrophils on influenza virus propagation was also investigated.…”
mentioning
confidence: 98%
“…The antifungal activity of calprotectin is inhibited by the presence of zinc ion and the factor has a zinc-binding property 50,51) ; in fact, there are zinc-binding motifs in the subunit peptides. 52) This suggests that the factor withholds zinc from the growth media of fungi, because fungi strongly require zinc for their growth.…”
Section: )mentioning
confidence: 99%
“…Together, these activities indicate a putative role in regulating leukocyte migration to inflammatory sites. S100A8/A9 is also known to inhibit microbial growth, presumably by chelating zinc (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and to inhibit bacterial adhesion to mucosal epithelial cells (34). Thus, it is reasonable to propose a role in innate immune responses to bacterial infections for these molecules.…”
mentioning
confidence: 99%